Talking with the dead: revisiting the Victorian past and the occult in Margaret Atwood’s Alias Grace and Sarah Waters’ Affinity1 - Arias Doblas, Rosario (Estudios Ingleses de la Universidad Complutense, 2005)
This paper undertakes the examination of Margaret Atwood’s Alias Grace (1996) and Sarah Waters’s Affinity (1999) by focusing on the theme of spiritualism and mesmerism in each of the texts and what that reveals about the role of women in Victorian society and its literary representation in neo- Victorian fiction. It will be argued that this engagement with the occult can be understood as a metaphor for the postmodern idea of resurrecting Victorian concerns in what appears to be a literary subset of the neo-Victorian novel, the spectral novel, a textual space for fictionalising what is absent from historical record and for making the dead speak in manifold ways. In this sense, Atwood and Waters, who can be considered historians in their archeological project of digging out the past, assume the role of the medium in establishing the dialogue between the past (the world of the dead) and the present (the world of the living).